Answer:
7 ÷ 5
Step-by-step explanation:
1/5 of 7 is equal to 1/5 times 7/1, which will simplify to 7/5, or 7 ÷ 5.
Step-by-step explanation:
Inverse of
y
=
x
+
3
x
−
2
is
y
=
2
x
+
3
x
−
1
Explanation:
As
y
=
x
+
3
x
−
2
x
y
−
2
y
=
x
+
3
or
x
y
−
x
=
2
y
+
3
or
x
(
y
−
1
)
=
2
y
+
3
or
x
=
2
y
+
3
y
−
1
Hence inverse of
y
=
x
+
3
x
−
2
is
y
=
2
x
+
3
x
−
1
Observe that each of the function is a reflection of the other in the line
x
=
y
.
graph{(y-(x+3)/(x-2))(y-(2x+3)/(x-1))(x-y)=0 [-10, 10, -5, 5]}
The correct answer would be: 18+18i